Prospektif Monitoring Terhadap Kejadian Dispensing Error Pada Obat Antibiotik di Instalasi Gawat Darurat (IGD) RSUP Fatmawati Periode April 2026 - Moh. Abdul Basith Nawawi Azan (RSUP Fatmawati, 2026)
Infectious diseases remain a significant health problem in Indonesia, leading to increased use of antibiotics and posing risks of inappropriate therapy and antimicrobial resistance. This study aims to evaluate the appropriateness of antibiotic distribution at the dispensing stage in the Emergency Department of RSUP Fatmawati based on the five rights principle. The method used was prospective observation with monitoring during the period of April 2026 on the antibiotic dispensing process, including preparation, final check, and drug delivery, supported by interviews with pharmacy personnel. The study sample included 109 injectable antibiotic prescriptions, namely ceftriaxone, meropenem, ciprofloxacin, and cefotaxime. The research results show that all accuracy parameters (right patient, medication, dose, time, and route) reached 100%. The most commonly used antibiotic was ceftriaxone (60.55%), followed by meropenem (33.95%), ciprofloxacin (3.67%), and cefotaxime (1.83%), with a dominance of the Watch group based on the AWaRe classification. The high level of distribution accuracy is influenced by the experience of pharmaceutical personnel as well as the implementation of good standard operating procedures. In conclusion, the antibiotic dispensing process in the emergency department of Fatmawati Hospital has complied with the five-right principles and supports rational use of antibiotics.